WinRoots: A High-Throughput Cultivation and Phenotyping System for Plant Phenomics Studies Under Soil Stress - Zhang, Yangyang; Zhang, Wenjing; Cao, Qicong; Zheng, Xiaojian; Yang, Jingting; Xue, Tong; Sun, Wenhao; Du, Xinrui; Wang, Lili; Wang, Jing; Zhao, Fengying; Xiang, Fengning; et al. (Frontiers in Plant Science, 2022)
Soil stress, such as salinity, is a primary cause of global crop yield reduction. Recently developed high-throughput sequencing technologies have empowered multi-omics association analysis as an effective strategy for mining functional genes underlying key agronomic traits and whole-genome selection to accelerate crop breeding. However, the acquisition of accurate high-throughput phenotypic data is currently a bottleneck. Existing crop phenotyping platforms also cannot fully meet the specific needs of phenomics studies of plant response to soil stress in terms of throughput, environmental controllability, or root phenotypic acquisition. Here, we report the WinRoots, a low-cost and high-throughput plant soil cultivation and phenotyping system that can provide uniform, controlled soil stress conditions and accurately quantify the whole-plant phenome, including roots. Using soybean seedlings exposed to salt stress as an example, we demonstrate the uniformity and controllability of the soil environment in this system. A high-throughput multiple-phenotypic assay among 146 soybean cultivars reveals that the cotyledon character can serve as a non-destructive indicator of the whole-seedling salt tolerance. Our results demonstrate that WinRoots is an effective tool for high-throughput plant cultivation and soil stress phenomics studies.